ANALISIS EMISI GAS BUANG HASIL PEMBAKARAN SOLAR DAN BIOSOLAR (B25) PADA FIRE TUBE BOILER - Winny Andalia Andalia (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
The use of biodiesel in boilers has great benefits because it reduces exhaust emissions. The purpose of this study is to test the quality of solar and biosolar raw materials as fuel from the boiler, analyze the concentration of pollutant gases (NOx, CO2, SO2) from the combustion of biosolar and diesel oil experimentally. The combustion system in the boiler tends to be simpler than compression ignition as is done with diesel engines. This research was conducted experimentally in a fire tube boiler, with a heat input rate of 60,000 kCal / hour and a pressure of 3 bar using biodiesel made from CPO (crude palm oil) as fuel. The mixture varies at 0, 5, 10, 15, 20 and 25% biodiesel in a mixture with biosolar diesel (B0, B5, B10, B15, B20 and B25). This research was carried out experimentally by testing the exhaust gas emissions generated from the stack gas stack which is expected to produce low exhaust emissions and are environmentally friendly. The results show that the use of biodiesel reduces gas emissions by increasing the value of biodiesel in the mixture. The results showed that the lowest gas emissions were around 4.142% (NOx); 12.50% (SO2) and 7.9% (CO2) contained in a mixture of 25% biodiesel in fuel (B25).